Pattern recognition using transabdominal ultrasound to diagnose ovarian mature cystic teratoma - Tongsong T. (2014)
Objective: To determine the validity of sonographic pattern recognition in the diagnosis of mature cystic teratoma. Methods: Consecutive patients scheduled for elective surgery for adnexal masses were included in the study. All patients underwent transabdominal ultrasound with color extended-flow mapping within 24 hours prior to surgery. Examinations were performed by the same sonographer to identify benign cystic teratoma. The final diagnoses were based on histopathologic findings. Results: A total of 329 consecutive patients were recruited; 23 were excluded because the masses were not adnexal masses. Of the remaining 306 patients, 36 masses were found to be mature cystic teratomas and 270 were nonteratomas. Sonographic pattern recognition showed a sensitivity of 94.4% and a specificity of 98.2%. Conclusion: Sonographic pattern recognition using transabdominal ultrasound with color extended-flow mapping can accurately diagnose mature cystic teratoma. © 2008 International Federation of Gynecology and Obstetrics.